The impact of climate change on the economic perspectives of crop farming in Pakistan: Using the ricardian model. (25th July 2021) - Ali, Uzair; Wang, Jing; Ullah, Arif; Ishtiaque, Asif; Javed, Tehseen; Nurgazina, Zhanar
Abstract: Climate change may have detrimental effects on income from crop farming in Pakistan and according to the IPCC (2014), the impacts of climate change will be more vigorous in the coming years. Despite a few studies we still have limited knowledge on how climate change can impact the crop farming economy in Pakistan. Considering Khyber Pakhtunkhwa (KP) province of Pakistan as the study area, we attempted to fill this gap by analyzing the economic impacts of climate change on the net income from crop farming. Data from the 635 farm households and also climatic variables data were collected from five agro-ecological zones (AEZ) of the KP. The Ricardian method was employed for analysis purposes. The results revealed that the increase of annual average temperature and decreases in rainfall is strongly associated with net revenue deficits. The effects of increasing precipitation are observed to be useful but an increase in temperature is forecasted to be harmful to the net revenue. The effect of increased temperature in the summer season on NR ranged between US$-29 to US$35, and the effect in the winter season ranged between US$-14 to US$28 per hectare. The effect of decreased annual precipitation on NR in the summer season and winter season ranged between US$ 0 to US$-24 and US$<-20 per hectare, respectively. This effect is particularly severe in the Central Valley Plains, Southern Piedmont Plains, and Western Dry Mountains. This study further evaluates the effects of the climatic forecasts by three Atmospheric Oceanic General Circulation Models (AOGCM). Our results will facilitate the policymakers to implement suitable strategies in KP to curb the deleterious effects of climate change on overall crop production and farmer income.